(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: In Southwark (London), 68.9% of residents are physically inactive. Southwark Council’s Integrated Healthy Lifestyle Service (IHLS) offers a single point of access for residents to health services (e.g. exercise referral). Referrals are managed by the Healthy Lifestyle Hub (HLH), a telephone-based triage service aiming to enhance referral efficiency and follow-up, supporting behaviour change. One of the local services the HLH refers onto is Exercise on Referral (EoR). The aim of this evaluation is to understand how Southwark Council’s HLH influences referral to and engagement in EoR. Methods: We conducted a mixed-methods evaluation, informed by public and stakeholder consultation. Work package (WP)1 involved secondary analysis of referral, attendance, and health data from HLH and EoR; WP2 involved an online survey of HLH users, exploring reasons for non-initiation of referrals (descriptive/inferential statistics were performed as data allowed for WP1/2); WP3 involved semi-structured interviews and focus groups with service users, staff, and non-initiators to explore service experiences (codebook thematic analysis). Results: The data shared from WP1 highlighted inconsistencies in data linkage and a high degree of missing follow-up data, making it challenging to determine any objective changes in behaviour or health. Survey data (WP2) was available for 163 people, with seven individuals providing information on why they were referred to EoR but did not intend on initiating the service (e.g. inappropriate day/time). WP3 findings found that service users experienced benefits including weight loss and improved mental health. However, they felt the duration was insufficient for behaviour change. Service users stated a lack of affordable post-programme options. Key service recommendations included improving data collection and linkage, extending post-programme support, improving communication with service users, and clarifying referral. Conclusion: Implementation of these recommendations will improve programme accessibility and engagement, behaviour change and health outcomes, and, importantly, the ability to accurately evidence changes. Wider implementation of community-led programmes align with sustainability development goals 3 and 10. Support/Funding Source: This project is funded by the NIHR [Public Health Research programme (NIHR 166241)/PHIRST Elevate NIHR160288]. The views expressed are those of the authors and not necessarily those of the NIHR or the Department of Health and Social Care.